Role of Anticonvulsants in the Management of Posttraumatic Epilepsy - Kirmani, Batool F.; Robinson, Diana Mungall; Fonkem, Ekokobe; Graf, Kevin; Huang, Jason H. (Frontiers in Neurology, 2016)
Posttraumatic seizures have been recognized as a major complication of traumatic brain injury. The annual incidence of traumatic brain injury in the United States is 1.7 million. The role of anticonvulsants in the treatment of posttraumatic epilepsy remains uncertain. Based on current studies however, anticonvulsants have been shown to reduce early posttraumatic seizures occurring within the first seven days, but little to no benefits have been shown in late posttraumatic seizures occurring after 7 days. In this paper, we provide a minireview of the role of anticonvulsants and current advances in the management of posttraumatic epilepsy.